2009
DOI: 10.1158/1078-0432.ccr-08-2581
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Blocks Cisplatin-Induced Apoptosis and Predicts Poor Outcome Following Chemoradiation Treatment in Advanced Oropharyngeal Squamous Cell Carcinoma

Abstract: Purpose:This study aimed to test the hypothesis that elevated expression of antiapoptotic Bcl-2 family proteins predicts a poor therapeutic response of oropharyngeal squamous cell carcinoma (OPSCC) to concurrent platinum-based chemoradiation therapy. Experimental Design: Levels of Bcl-2, Bcl-X L , and Bcl-w were determined and correlated with resistance to cisplatin in a large panel of cell lines derived from squamous cell carcinoma of the head and neck (HNSCC). Univariate and multivariate analyses were used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 44 publications
8
71
0
Order By: Relevance
“…22) In this study, down-regulation of Bcl-2 and Bcl-XL and up-regulation of Bax and Bad were detected in the presence of BSBD (Fig. 3C).…”
Section: Resultssupporting
confidence: 57%
“…22) In this study, down-regulation of Bcl-2 and Bcl-XL and up-regulation of Bax and Bad were detected in the presence of BSBD (Fig. 3C).…”
Section: Resultssupporting
confidence: 57%
“…In HNSCC cell lines, we found that high expression of the antiapoptotic protein Bcl2 enhanced tumor-cell survival, in particular after treatment with cisplatin (12,13). We extended these findings to advanced OPSCC treated with platinum-based concurrent chemoradiation, a current standard of care (9,14,15), and determined that high pretreatment tumor expression of Bcl2 predicted worse clinical outcome (13).…”
mentioning
confidence: 76%
“…For instance, conclusive clinical data on the association between the proapoptotic BCL-2 family members BAX and BAK and cisplatin sensitivity are missing, but elevated levels of their antiapoptotic counterparts including BCL-2, BCL-X L and MCL-1 (myeloid cell leukemia sequence 1) reportedly correlate with cisplatin resistance and tumor recurrence in multiple clinical scenarios, including head and neck cancer, ovarian cancer and NSCLC (Han et al, 2003;Erovic et al, 2005;Williams et al, 2005;Michaud et al, 2009). Moreover, ongoing clinical trials are evaluating the combination of cisplatin with small molecules that inhibit BCL-2-like proteins (for example, ABT-263, ABT-737) for the treatment of several neoplasms (Jain and MeyerHermann, 2011).…”
Section: Chemoresistance To Cisplatin L Galluzzi Et Almentioning
confidence: 99%